Planning for educators and educational staff in character-based islamic schools at SMA Cahaya Rancamaya Islamic Boarding School Bogor - Irwansyah; Endin Mujahidin; Nesia Andriana; Wahida Begum (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The study employed a qualitative method with purposive sampling to determine data sources. This approach was used to analyze the planning, recruitment, placement, training, and evaluation processes of educators and staff at SMA Cahaya Rancamaya Bogor, a school integrating three curricula (Islamic, national, and Cambridge). Needs analysis, job analysis, workload analysis, and task specifications revealed that the school requires educators such as Qur'an teachers, homeroom teachers, subject teachers, and English and Arabic teachers. The support staff comprises administrative personnel, operators, janitors, and security staff. The recruitment process involves a rigorous selection procedure, including administrative, skill, and interview tests, as well as the Academy of Future Teachers (AFT) program in collaboration with Eduversal. Placement is based on competency and experience, while training is structured, covering technical skills, teaching methods, and spiritual development. Performance evaluation includes reward systems to enhance motivation and a tiered punishment process for rule violations.The criteria for educators and staff are designed to align with the school’s vision of becoming an independent, excellent, modern, and dynamic Islamic institution. This comprehensive process aims to create competent and exemplary personnel to support learning and student development.